The development of a task to study advice taking across nations and its application in a China-Germany comparison - Thomas Schultze; Zhijun Chen (Judgment and Decision Making)
Advice taking is a crucial part of decision-making and has attracted the interest of scholars across the world. Laboratory research on advice taking has revealed several robust phenomena, such as sensitivity to advice quality or a tendency to underutilize advice. Despite extensive investigations in different countries, cultural differences in advice taking remain understudied. Knowing whether such cultural differences exist would not only be interesting from an academic standpoint but might also have consequences for multinational organizations and businesses. Here, we argue that prior laboratory research on cultural differences in advice taking is hindered by confounding factors, particularly the confound between participants’ cultural background and task difficulty. To draw a valid conclusion about cultural differences in advice taking, it is vital to develop a decision task devoid of this confound. Here, we develop such a judgment task and demonstrate that the core phenomena of advice taking manifest in a sample of German participants. We then use this task in a cross-national comparison of German and Chinese participants. While the core phenomena of advice taking consistently manifested in both samples, some differences emerged. Most notably, Chinese participants were more receptive of advice, even though they still underutilized it. This greater reliance on advice was driven by Chinese participants’ greater preference for averaging their own and the advisor’s judgments. We discuss how our findings extend current understanding of the nuanced interplay between cultural values and the dynamics of advice taking.